2019
DOI: 10.1002/bmc.4744
|View full text |Cite
|
Sign up to set email alerts
|

A biochemometrics strategy for tracing diuretic components of crude and processed Alisma orientale based on quantitative determination and pharmacological evaluation

Abstract: We proposed a biochemometrics strategy for tracing diuretic components of herbs based on quantitative determination and pharmacological evaluation. First, a sensitive and robust liquid chromatography coupled with tandem mass spectrometry approach was established for simultaneous quantification of six major triterpenoids in crude and salt‐processed Alisma orientale. The separation of triterpenoids was achieved on a BEH C18 column with a mobile phase consisting of acetonitrile and water spiked with 0.1% formic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In addition, the contents of type I (compound 48 , 50 , 54 , 56 , 62 , 70 , and 81 ) and type III (compound 26 , 30 , 40 , 58 , and 103 ) triterpenes with hydroxyl or acetyl groups at C 23 , C 24 , and C 25 were significantly reduced after salt-processing. It was reported that the compounds with substituting groups, such as hydroxyl and acetyl groups, would lose H 2 O and AcOH under high temperature [ 16 , 19 ]. Moreover, there was the evidence suggesting that the total contents of triterpenes were decreased with the baking temperature increasing, especially when the temperature was above 80 °C [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the contents of type I (compound 48 , 50 , 54 , 56 , 62 , 70 , and 81 ) and type III (compound 26 , 30 , 40 , 58 , and 103 ) triterpenes with hydroxyl or acetyl groups at C 23 , C 24 , and C 25 were significantly reduced after salt-processing. It was reported that the compounds with substituting groups, such as hydroxyl and acetyl groups, would lose H 2 O and AcOH under high temperature [ 16 , 19 ]. Moreover, there was the evidence suggesting that the total contents of triterpenes were decreased with the baking temperature increasing, especially when the temperature was above 80 °C [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the processing, complicated changes in herbal components may occur, and the pharmacological activity of a certain herbal medicine may be changed accordingly [ 1 ]. Previous studies demonstrated that SAR showed a better hepatoprotective activity and diuretic effect than crude AR [ 16 , 26 ]. This phenomenon also occurs in other salt-processed plant medicine [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the extract of A. orientale (IC 50 = 22.0 μg/ml) had a strong inhibitory effect against the Na + /K + ‐ATPase of kidney (Satoh et al, 1991). Tao et al obtained alisols A, B, and F from A. orientale and found that they had diuretic effects (Tao, Jiang, Yan, & Cai, 2020). Subsequently, Zhang et al evaluated the diuretic effects of total triterpenoids of A. orientale .…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%